A reverse transcriptase ribozyme - Samanta, Biswajit (eLife, 2017)
A highly evolved RNA polymerase ribozyme was found to also be capable of functioning as a reverse transcriptase, an activity that has never been demonstrated before for RNA. This activity is thought to have been crucial for the transition from RNA to DNA genomes during the early history of life on Earth, when it similarly could have arisen as a secondary function of an RNA-dependent RNA polymerase. The reverse transcriptase ribozyme can incorporate all four dNTPs and can generate products containing up to 32 deoxynucleotides. It is likely that this activity could be improved through evolution, ultimately enabling the synthesis of complete DNA genomes. DNA is much more stable compared to RNA and thus provides a larger and more secure repository for genetic information.